Effects of molasses addition to ration on the productivity of Kacang goats - Martawidjaja, MuchJi; Setiadi, B; Sitorus, S (Indonesian Journal of Animal and Veterinary Sciences, 1998)
The experiment was conducted in Cilebut Experiment Station, Bogor, with the aim to improve the productivity of Kacang goats. Twenty male goats, 9-10 months old, with an average initial liveweight of 16.27 kg were used. The goats were randomly divided into four treatments with five animals each, and were kept by grouped pen system. The dietary treatments were: (R0) = Elephant grass (EG) + concentrate (C0), (R1) = EG + (95% C0 + 5% molasses), (R2) = EG + (90% C0 + 10% molasses), (R3) = EG + (85% C0 + 15% molasses), respectively. The Elephant grass was offered ad libitum while the concentrate was offered at 3% of total body weight per treatment group. The experiment was carried out for 14 weeks. Feed intake per treatment group, individual weight gain, and feed conversion were analyzed. Average daily gain was analyzed in a completely randomized design. The results indicated that R0 (0% molasses), R1 (5% molasses), R2 (10% molasses) and R3 (15% molasses), did not significantly affect the average daily weight gain (P>0.05) with an overall mean of ADG to be 55.6 g/head/day. Feed intake and feed conversion were not significantly different among dietary treatments with an average dry matter intake of 2,621 g/5 heads/day or 524 g/head/day; protein intake was 370 g/5 heads/day or 74.0 g/head/day with energy intake of 10.929 Mcal/5 heads/day or 2.186 Mcal/head/day, and feed conversion of 9.43. In conclusion, the fact that molasses addition to rations did not affect feed intake, daily weight gain and feed conversion indicating that the molasses addition did not improve the Kacang goats fattening productivity. Â  Key words : Productivity, goats, molasses